Influence of soils, nutrition, and water relations upon charcoal rot disease processes in Kansas. - Cruz, David Ricardo Jimenez (Kansas State University, 2011)
Charcoal rot, caused by Macrophomina phaseolina, is the most important soybean disease in Kansas. Several strategies have been recommended to control this disease including crop rotation, lower plant densities, biological control, plant resistance and tolerance, and fungicide application. However, those techniques have not been completely effective and the information concerning soil texture, irrigation and micronutrient fertility (particularly manganese) upon charcoal rot disease severity and the pathogen population is limited. The objective of this study was to determine key factors that affect the biology of M. phaseolina and charcoal rot processes under laboratory, greenhouse and field conditions. M. phaseolina microsclerotia were produced from PDA pure isolate and infested Japanese millet in the laboratory and characterized by different techniques such as serial dilutions in semi selective media with the aim to produce quality inoculum to reliably infect soybean seedling roots under greenhouse conditions; production of inoculum by infesting Japanese millet was the most efficient method. Root colonization and root infection of soybean seedlings was assessed through the use of M. phaseolina inoculum under controlled conditions in the greenhouse. Root infection by M. phaseolina and microsclerotia longevity in soil is determined by environmental factors such as soil moisture content, soil texture and source of inoculum. The objective of the greenhouse study was to determine the impact of these variables on seedling root infection at the V1 and V2 development stages. Artificial soils with different textures were infested; M. phaseolina microsclerotia and soybean seedlings were exposed to different soil moisture contents including pot saturation, pot (field) capacity, and permanent wilting point. Soil populations and levels of root colonization for the stages were assessed by estimating CFUs and root length. Results indicate that soil texture has a significant impact upon root morphology and root length. Root populations of M. phaseolina were significantly higher in sandy soil textures and lower in the fine-textured soils, suggesting an impact of soil water holding capacity in the root infection process. The effect of water stress on seedling root colonization by M. phaseolina indicates that early infection may be more important than previously thought. A field study was also conducted to determine the effect of the aforementioned variables in a 2-year field experiment conducted at two Kansas locations. Pathogen colonization was iii assessed by measuring colony-forming units (CFUs) from ground root tissue at R2-R4 (post-flowering/early pod development) and R8 (maturity) stages. Soil populations (pre-planting and post-harvest) of M. phaseolina, yield parameters, and plant characteristics were obtained. Results indicated that there are complex relationships between soil physiochemical properties (pH, NPK content, exchangeable cations, and organic matter) and soil texture (sand, soil, and clay composition), which may mitigate disease severity and pathogen levels in host tissue. Results also indicated that in natural M. phaseolina-infested soils, cropping history and soil texture play an important role in charcoal rot processes and influence the levels of pathogen soil populations, root colonization at maturity and, more importantly, soybean yield.
Keywords: Macrophomina; Phaseolina; Soybean; Soil; Water; Plant Pathology (0480)